La Guerra Civil española, un hito en la historia de la propaganda - Alejandro Pizarroso Quintero (El Argonauta Español, 2005)
The phenomenon of propaganda is closely connected to the history of war. If propaganda had been a fundamental weapon during World War I, during the Spanish Civil war, its role was even more important, because of its ideological dimension. This article analyzes the basic concepts of war propaganda, and presents the type of organization and the various means, which the Republicans and the Franquists used to diffuse their propaganda to the populations away from the front line, to the enemy and also in foreign territory.